2023
DOI: 10.1039/d3ra02399k
|View full text |Cite
|
Sign up to set email alerts
|

Surface modified nanoparticles and their applications for enantioselective detection, analysis, and separation of various chiral compounds

Abstract: The combination of surface-modified nanomaterials and chiral selectors can improve enantioselective recognition with a significant influence on the performance of enantioselective detection, analysis, and separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…29,50,132,192–194 However, the increasing interest in employing chiral nanomaterials for biomedical applications has driven research on the chiral interactions between materials and living systems. 195–199 For example, recent studies have reported the development of chiral AuNPs to direct immune responses 38 and the ability of chiral materials to modulate stem cell differentiation and different levels of enzymatic activities. 200,201 In this section, we survey the most recent studies in the small but rapidly expanding field of chiral nanomaterials in tissue engineering, focusing on their applications in the regeneration of various types of tissues.…”
Section: Chiral Nanomaterials In Tissue Engineeringmentioning
confidence: 99%
“…29,50,132,192–194 However, the increasing interest in employing chiral nanomaterials for biomedical applications has driven research on the chiral interactions between materials and living systems. 195–199 For example, recent studies have reported the development of chiral AuNPs to direct immune responses 38 and the ability of chiral materials to modulate stem cell differentiation and different levels of enzymatic activities. 200,201 In this section, we survey the most recent studies in the small but rapidly expanding field of chiral nanomaterials in tissue engineering, focusing on their applications in the regeneration of various types of tissues.…”
Section: Chiral Nanomaterials In Tissue Engineeringmentioning
confidence: 99%